Canakinumab (ACZ885, a fully human IgG1 anti-IL-1β mAb) induces sustained remission in pediatric patients with cryopyrin-associated periodic syndrome (CAPS) - Kümmerle-Deschner, Jasmin; Ramos, Eduardo; Blank, Norbert; Roesler, Joachim; Felix, Sandra D.; Jung, Thomas; Stricker, Kirstin; Chakraborty, Abhijit; Tannenbaum, Stacey; Wright, Andrew M.; Rordorf, Christiane (Arthritis Research & Therapy, 2011)
Cryopyrin-associated periodic syndrome (CAPS) represents a spectrum of three auto-inflammatory syndromes, familial cold auto-inflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS), and neonatal-onset multisystem inflammatory disease/chronic infantile neurological cutaneous and articular syndrome (NOMID/CINCA) with etiology linked to mutations in the NLRP3 gene resulting in elevated interleukin-1β (IL-1β) release. CAPS is a rare hereditary auto-inflammatory disease, which may start early in childhood and requires a life-long treatment. Canakinumab, a fully human anti-IL-1β antibody, produces sustained selective inhibition of IL-1β. This study was conducted to assess the efficacy, safety, and pharmacokinetics of canakinumab in the treatment of pediatric CAPS patients.